Massive MIMO LEO Satellite Communications System - Kexin LI; Li YOU; Xiqi GAO (天地一体化信息网络)
Extending massive multiple-input multiple-output (MIMO) technique to low earth orbit (LEO) satellite communication systems enables satellites to implement fl exible beamforming, which can make full use of the spatial degrees of freedom of massive MIMO and signifi cantly improve the spectral effi ciency and energy effi ciency of LEO satellite communication systems.Several related issues in massive MIMO-based LEO satellite communication systems were studied.The characteristics of massive MIMO LEO satellite channels were analyzed.The important diff erences between them and terrestrial wireless channels were revealed.With the aim of addressing the problems on channel information acquisition, multi-user transmission and user scheduling in massive MIMO LEO satellite communication, the main difficulties faced by the current work were discussed, and how to use the characteristics of massive MIMO LEO satellite channels to design tailored solutions with low implement complexity was conceived.